The Meaning of the Elderly Sexuality in the Nursing Consultation Context. - Saraiva, Renata (2017)
Objective: Comprehend the meaning of the elderly sexuality in the nursing consultation context. Method: A qualitative research, of Alfred Schutz’s phenomenological sociological approach. 41 participants, being Brazilian and Portuguese elderly. The used scene was the teaching-assistance academic unit Institute of Health Care São Francisco de Assis – Rio de Janeiro – Brazil and Health School – Polytechnical Institute of Guarda – Portugal. Results: The analysis of the contextualization of the reason-why and its categories: Interpretations of sexuality and sex between elderly; Cultural aspects involved among the elderly. Conclusion: The lack of correct interpretation between the sexuality meaning and sex contributes to the insight of preventive clinical care, just as for sex-related pathologies.